Λ(t) cosmology induced by a slowly varying Elko field - Pereira, S. H. [UNESP]; Pinho SS, A. [UNESP]; Hoff Da Silva, J. M. [UNESP]; Jesus, J. F. [UNESP] (IOP Publishing, 2017)
In this work the exact Friedmann-Robertson-Walker equations for an Elko spinor field coupled to gravity in an Einstein-Cartan framework are presented. The torsion functions coupling the Elko field spin-connection to gravity can be exactly solved and the FRW equations for the system assume a relatively simple form. In the limit of a slowly varying Elko spinor field there is a relevant contribution to the field equations acting exactly as a time varying cosmological model Λ(t) = Λ∗ + 3βH2, where Λ∗ and β are constants. Observational data using distance luminosity from magnitudes of supernovae constraint the parameters Ωm and β, which leads to a lower limit to the Elko mass. Such model mimics, then, the effects of a dark energy fluid, here sourced by the Elko spinor field. The density perturbations in the linear regime were also studied in the pseudo-Newtonian formalism.
Keywords: Cosmology of theories beyond the SM; Dark energy theory; Supernova type Ia - standard candles